DEVELOPMENT OF MARKETING IN AZERBAIJAN - MAHARRAMLI , Subhi Ilqar oğlu (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The main goal of the article is to study activities aimed at marketing development in Azerbaijan. It is noted that benefiting from the synthesis of the national characteristics of the economy (including the experience of the Soviet era) and the world experience is one of the urgent requirements of the modern era. Method and methodologies. In the analysis process, comparative analysis of statistical indicators, analysis of legal-normative documents necessary for the development of marketing, classification of existing problems in the system of formation of market relations in Azerbaijan, forecasting and projecting methods were used. Novelty on the article. The article focuses on some rational and non-rational activities that are neglected in the scientific literature and necessitates the development of marketing. Conclusion and suggestions. The article emphasizes that marketing promotion is a step that serves to make companies popular among the population. These steps are one of the necessary steps to be carried out and updated both thoroughly and systematically. It is noted that 90% of managers of companies operating in Azerbaijan think that there is no need for marketing research. Thus, the decision to implement marketing measures is not based on the analysis of research data, and this, in turn, does not justify the effectiveness of marketing projects. Businessmen rely too much on their intuition and make unreasonable expenses based only on their own experience and unsystematized information that reaches them over a period of time. As a result: 1. Unsuccessful image campaigns are organized that do not produce any desired intangible effect; 2. Sales of newly launched products are falling; 3. Preference is given to advertising campaigns mainly aimed at financial impact; 4. Absurd models of brand perception emerge as a result of lack of study of brand perception after marketing activities; 5. Low level of service and, as a result, customer satisfaction. At best, marketers refer to a company’s to-do list.